Dual suction Headway27 microcatheter thrombectomy for the treatment of distal intracranial arterial occlusion strokes: initial experience with the micro-ADAPT technique. (24th November 2018) - Crockett, Matthew Thomas; Phillips, Timothy John; Chiu, Albert Ho Yuen
Abstract : Background: Recent studies suggest that the proven benefits of endovascular thrombectomy (EVT) for the treatment of large vessel occlusion (LVO) strokes are transferable to more peripheral distal vessel occlusion (DVO) strokes under certain circumstances. Safely accessing and extracting these thrombi however remains challenging, particularly in more tortuous peripheral arteries. For such cases we have utilized the dual suction Headway27 microcatheter thrombectomy, or micro-ADAPT, technique with the aim of reducing potential trauma associated with negotiating stent retrievers or large bore aspiration catheters into the peripheral intracranial vasculature. We present our experience utilizing the micro-ADAPT in the treatment of DVO strokes. We describe our technique as well as present angiographic and clinical outcomes. Methods: A retrospective review of our institution's prospectively collected EVT registry for the 12 months spanning July 2017 to June 2018 was undertaken. Data on all cases of micro-ADAPT EVT were collected and analyzed. Results: Micro-ADAPT EVT was performed 14 times over the study period, with a recanalization rate of 79%. DVO strokes in multiple locations were treated, including the A3, M3, P3, and superior cerebellar artery. In cases where an LVO stroke was also present, the mean duration between primary LVO recanalization and secondary DVO micro-ADAPT recanalization was 15.5 min. No complications relating to the micro-ADAPT technique were recorded. No infarcts were present in the territory of the recanalized DVO stroke on day 1 CT in successful micro-ADAPT cases Conclusions: In the setting of challenging peripheral DVO strokes, the micro-ADAPT technique appears to be a fast and effective technique with a low complication rate.